2015
DOI: 10.1007/s10943-015-0117-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Black Churches’ Readiness to Address HIV

Abstract: This study employed a community-based participatory research approach to understand factors that influence church readiness to engage in HIV prevention and treatment activities. A convenience sample of twenty-six Black faith leaders participated in four focus groups. Data analysis was done through qualitative content analysis. Three themes emerged. First, the pastor's blessing and authority as the church's decision-maker determines readiness to engage in HIV prevention. Second, the church's purview of sexual h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Prior research has shown that when stigma around their sexuality is present in churches, Black gay and bisexual men might suffer from social isolation and an unwillingness to seek guidance from their church leadership [ 14 ]. Stigma around sexuality has also been known to ignite fears of losing congregants among some pastors [ 12 , 34 ]. A church case study in the Midwest, assessing barriers that clergy experienced in starting and sustaining an HIV ministry, found that the primary barrier was views regarding sexuality [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research has shown that when stigma around their sexuality is present in churches, Black gay and bisexual men might suffer from social isolation and an unwillingness to seek guidance from their church leadership [ 14 ]. Stigma around sexuality has also been known to ignite fears of losing congregants among some pastors [ 12 , 34 ]. A church case study in the Midwest, assessing barriers that clergy experienced in starting and sustaining an HIV ministry, found that the primary barrier was views regarding sexuality [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The robust literature demonstrates churches are providing congregations and their surrounding community access to HIV education, prevention, and testing, which often is informed by biblical principles [ 9 , 10 ]. There are a number of factors facilitating readiness to address HIV, including having the blessing and support of the church leadership, purview on sexual health, and resources to implement prevention [ 11 , 12 ]. Yet a notably, well-documented social challenge remains—stigma—which disrupts people living with HIV from accessing care and serves as a threat to public health [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there have been a growing number of faith-based HIV interventions, nearly all in AA churches (Abara, Coleman, Fairchild, Gaddist, & White, 2015; Berkley-Patton et al, 2010; Berkley-Patton et al, 2016; Francis & Liverpool, 2009; Griffith, Campbell, Allen, Robinson, & Stewart, 2010; Lindley, Coleman, Gaddist, & White, 2010; Wooster et al, 2011). Many barriers to HIV programs in faith-based settings exist, including HIV-related attitudes and stigma, low HIV knowledge, lack of experience with HIV programming, lack of lay leadership and congregant support, and financial barriers (Coleman, Lindley, Annang, Saunders, & Gaddist, 2012; Cunningham, Kerrigan, McNeely, & Ellen, 2011; Derose et al, 2014; Mendel et al, 2014; Pichon, Powell, Ogg, Williams, & Becton-Odum, 2016; Pryor, Gaddist, & Johnson-Arnold, 2015; Smith, Simmons, & Mayer, 2005; Williams, Pichon, Latkin, & Davey-Rothwell, 2014; Wooster et al, 2011). AA faith leaders have also expressed concerns about HIV prevention strategies (e.g., discussing condoms and sexual education) that may be viewed as conflicting with doctrine (Nunn et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found barriers to and facilitators of implementing church-based HIV programs in racial/ethnic minority communities; however, the research questions for these studies were derived from congregant perspectives on HIV-related stigma, HIV prevention, or HIV screening promotion interventions (Berkley-Patton, Moore, et al, 2013; Berkley-Patton, Thompson, et al, 2013; Pichon & Powell, 2015; Pichon, Powell, Ogg, Williams, & Becton-Odum, 2016; Pryor, Gaddist, & Johnson-Arnold, 2015; Williams et al, 2016). These studies left many unanswered questions about church leader perspectives on the feasibility of a focus on HIV care in African American churches.…”
mentioning
confidence: 99%